Micropattern-controlled chirality of focal adhesions regulates the cytoskeletal arrangement and gene transfection of mesenchymal stem cells. (April 2021) - Wang, Yongtao; Yang, Yingjun; Wang, Xinlong; Yoshitomi, Toru; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Cell chirality has been demonstrated to be important for controlling cell functions. However, it is not clear how the chirality of the extracellular microenvironment regulates cell adhesion and cytoskeletal structures and therefore affects gene transfection. In this study, the chirality of focal adhesions and the cytoskeleton of single human mesenchymal stem cells (hMSCs) was controlled by specially designed micropatterns, and its influence on gene transfection was investigated. Micropatterns with different cell adhesion areas and swirling stripe lines were prepared by micropatterning fibronectin on polystyrene surfaces. The chiral micropatterns induced the formation of chiral focal adhesions and chiral cytoskeletal structures. Gene transfection efficiency was enhanced with increasing adhesion area, while hMSCs on left-handed and right-handed swirling micropatterns showed the same level of gene transfection. When the swirling angle was changed from 0°, 30°, and 60° to 90°, the gene transfection efficiency at a swirling angle of 60° was the lowest. The influence of cell chirality on gene transfection was strongly associated with cellular uptake capacity, DNA synthesis and cytoskeletal mechanics. The results demonstrated that cytoskeletal swirling had a significant influence on gene transfection. Graphical abstract: Image 1 Highlights: Chiral micropatterns were prepared from photo-reactive PVA through photolithography. Cell chirality was controlled by the micropatterns. The influence of cell chirality on exogenous gene transfection was investigated. The swirling angle of cell chirality significantly affected transfection efficiency. Different transfection efficiency was associated with cell mechanics and activity.